Development of nanobody-based DAS-ELISA and Au nanoparticle-based immunochromatographic test strip for highly sensitive detection of Chikungunya virus - Guo, Mengmeng; Song, Liyuan; Liu, Jingliang; Hu, Yating; Chen, Yihui; Fu, Guangcheng; Yuan, Hongyu; Li, Jianmin (Frontiers in Immunology, 2025)
IntroductionChikungunya virus (CHIKV) is a mosquito-borne alphavirus that causes severe disease in humans and animals and continues to pose a significant global public health threat. Current diagnostic methods primarily rely on detecting CHIKV-specific IgM and IgG antibodies; however, these methods are limited to the humoral immune phase following viral infection.To address the diagnostic gap during the window period before antibody response, we developed two antigen detection assays capable of directly detecting the CHIKV envelope protein (CHIKV-E), enabling early and rapid viral detection.MethodsIn this study, 20 nanobodies (Nbs) specifically binding to CHIKV-E protein were screened and identified from a constructed immune nanobody library using phage display technology. These Nbs were fused to human IgG1-Fc and expressed as recombinant Nb-Fc antibodies in Expi293F cells. Subsequently, the preferred Nb-Fc pairs (N055-Fc/N055-mIgG1-Fc and 10G4-Fc) were used to establish double-antibody sandwich ELISA (DAS-ELISA) and Au nanoparticle-based immunochromatographic test strip (AuNP-ICTS) assays.ResultsBoth the DAS-ELISA and AuNP-ICTS demonstrated high sensitivity for CHIKV-E. The two assays also exhibited exclusive specificity for CHIKV-E, showing no cross-reactivity with envelope proteins from four related alphaviruses or two co-circulating flaviviruses. Epitope mapping revealed that nanobodies N055 and 10G4 recognized distinct linear epitopes: N055 targets E1 Domain II, whereas 10G4 recognizes the E1 fusion loop with additional interactions in E1 Domain II and E2 Domain B. Quantitative sensitivity analysis indicated that both DAS-ELISA and AuNP-ICTS effectively detect CHIKV-E in serum, with limits of detection (LoD) of 49 pg/mL and 1.56 ng/mL, respectively-demonstrating superior sensitivity compared with existing antigen detection methods. Notably, the AuNP-ICTS method completes detection within 10 min, significantly improving efficiency.DiscussionCollectively, the developed DAS-ELISA and AuNP-ICTS assays overcome the limitations of conventional IgM/IgG serological methods, providing superior sensitivity and rapid detection capabilities that make them promising diagnostic tools for early CHIKV detection.